Where's the vision? Rescuing integrativeness to understand the language learning motivation of English-speaking EFL instructors living in South Korea. (June 2019) - Gearing, Nigel; Roger, Peter
Abstract: In researching second language (L2) learners' motivation, the traditional Gardnerian concept of integrativeness was readily applicable in a world where discrete L2 communities were often clearly identifiable. However, the growing dominance of global English has rendered this construct less relevant for the ever-increasing numbers of L2-English learners for whom there is no geographically-defined L2 community with which to integrate. This transformation of the language learning landscape has seen integrativeness reinterpreted as a concept more aligned with individuals' self-identification and future visions as L2 users. The demand for English teachers worldwide has led to large numbers of first-language English speakers finding such work outside their own countries, but their motivation to learn the languages of their host nations remains unexplored. Based on interviews with 14 English as Foreign Language (EFL) instructors in South Korea, the present study found that most lacked the clear future L2 self visions required to drive motivation. In such cases, the traditional concept of integrativeness also retains its explanatory value, particularly as participants tended to attribute their lack of motivation to elements of the broader society in which they were living. These findings have implications for research on similar cohorts operating in a globalized marketplace.